Ideal? inaktiv. - Schmidt, Herbert (De Gruyter Mouton, 2017)
The revision of the German Dictionary of Xenologisms (foreign words), scheduled to comprise 15 volumes, registers the central inventory of the foreign words and word families firmly established in German and traces their historical development from about 1450 to the immediate present. The dictionary is a standard work of reference for present-day German.